Photovoltaic welding strip detection method

Through a series of tests of photovoltaic welding tape detection methods, the corrosion performance of flux on welding tape was evaluated, and the problem of neglecting the impact of flux corrosion in the existing technology was solved, and the reliability evaluation of the use of flux in the production process of photovoltaic modules was achieved.

CN119915713APending Publication Date: 2025-05-02YINGLI ENERGY DEV CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510250638.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When detecting corrosion of photovoltaic welding tape, the prior art mainly focuses on the corrosion effect of the adhesive film on the welding tape, and ignores the impact of flux on the performance of the welding tape, resulting in the inability to effectively detect the corrosion effect of flux on the welding tape.

Method used

A photovoltaic welding tape detection method is provided to evaluate the corrosion performance of the welding tape in the flux environment, including the rate of change of breakage and resistance value through the steps of sample preparation, initial testing, flux soaking, environmental testing and final testing.

Benefits of technology

Through this detection method, the corrosion impact of flux on different welding tapes can be accurately verified, and the impact of flux used in the production process on the reliability of photovoltaic welding tapes and components can be judged, which will help standardize the use of flux.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a photovoltaic welding strip detection method, and belongs to the technical field of photovoltaic cells, and the photovoltaic welding strip detection method comprises the steps of sample preparation, initial testing, soldering flux soaking, environment testing, final testing and performance evaluation. According to the invention, through a series of tests of the photovoltaic solder strip in the soldering flux environment, the corrosion influence of the soldering flux on different solder strips can be accurately verified by replacing different solder strips, and the corrosion influence of different soldering fluxes on the photovoltaic solder strip can also be accurately verified; therefore, the influence of the soldering flux used in the assembly production process on the reliability of the photovoltaic solder strip and the photovoltaic assembly can be judged, the safe and efficient use of the soldering flux can be standardized, and the method has important guiding significance on the use of the soldering flux and the solder strip in the photovoltaic assembly production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic cells, and in particular relates to a photovoltaic welding ribbon detection method. Background Art

[0002] In photovoltaic modules, photovoltaic ribbon welding is used to realize the current convergence of solar cells and the electrical connection between solar cells. Photovoltaic ribbon is also called photovoltaic tin-coated ribbon, which is divided into convergence ribbon and interconnection ribbon. The ribbon is an important raw material in the welding process of photovoltaic modules. The quality of the ribbon will directly affect the current collection efficiency of the photovoltaic module and has a great impact on the power of the photovoltaic module.

[0003] During the module production process, flux needs to be sprayed on the surface of the soldering ribbon. After the module is prepared, the flux may remain on the photovoltaic soldering ribbon. Since the flux contains acidic components, it will corrode the photovoltaic soldering ribbon and affect the performance and service life of the photovoltaic module.

[0004] At present, most of the corrosion detection of photovoltaic solder ribbons focuses on the corrosion effect of the adhesive film on the photovoltaic solder ribbons, and ignores the influence of the flux on the performance of the photovoltaic solder ribbons. How to detect the corrosion effect of the flux on the photovoltaic solder ribbons has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] An embodiment of the present invention provides a photovoltaic soldering ribbon detection method, which is intended to detect the performance of the photovoltaic soldering ribbon after the soldering flux corrodes the soldering ribbon.

[0006] To achieve the above object, the technical solution adopted by the present invention is: to provide a photovoltaic welding ribbon detection method, comprising: Step 1, sample preparation: Cut off several sections of welding strips of the same length, and randomly weld the welding strips together in pairs to form n samples to be tested, and randomly number them as L1, L2...L(n-1), Ln in sequence; n is a positive integer; Step 2: Initial test of the sample to be tested: Perform a breaking force test on n / 4 samples to be tested, and record the initial breaking force values ​​obtained in the test as LL1, LL2, ... LLx in sequence for breaking force test; x is a positive integer from 1 to n / 4; The resistance value of n / 4 samples to be tested is tested, and the initial resistance values ​​obtained by the test are recorded as DZ1, DZ2, ..., DZy in sequence; y is a positive integer from 1 to n / 4; Step 3: Test the sample after it is soaked in flux: The remaining samples to be tested are immersed in the flux and subjected to corrosion test; Step 4: simulate the actual application environment of the solder strip and conduct UV light and aging tests; Step 5: Test the results after corrosion: Perform a breaking force test on the remaining n / 4 samples to be tested, and record the final breaking force values ​​of the test as LL (x+1), LL (x+2) ... LL (x+x) in sequence; The remaining n / 4 samples to be tested are tested for resistance value, and the final resistance values ​​obtained from the test are recorded as DZ(y+1), DZ(y+2)...DZ(y+y) in sequence; In step 6, based on the test results, the corrosion performance of the solder strip in the flux environment is evaluated: Initial test results: Initial breaking force: Linitial = (LL1+LL2+…LLx) / x; Initial resistance value: D initial = (DZ1 + DZ2 + ... DZy) / y; Final test results: The breaking force of the welding strip after corrosion: Lfinal = (LL (x + 1), LL (x + 2) ... LL (x + x)) / x; Resistance value of the welding strip after corrosion: Dfinal = (DZ (y+1), DZ (y+2)…DZ (y+y)) / y; The change rate of the solder strip after being corroded by flux: Change rate of breaking force after corrosion of welding strip: Lchange = (Linitial - Lfinal) / Linitial Resistance change rate after welding strip corrosion Dchange = (Dfinal-Dinitial) / Dinitial Result evaluation: If the breaking force change rate L changes ≥5%, the soldering strip and flux are judged to be unsuitable; If the resistance value change rate D is ≥5%, the soldering tape and flux are judged to be unsuitable.

[0007] In one achievable manner, in step 3, the remaining sample to be tested is immersed in the flux, and the process of performing the corrosion test includes: Simulate the actual application environment of the solder strip, immerse the sample to be tested in the flux, and the flux temperature should be maintained at 40-45°C; and leave the clamping sections at both ends of the sample to be tested exposed outside the flux for easy detection and clamping; Clamp the clamping sections at both ends of the sample to be tested, and apply a rated current of 12.5-13.5I to the sample to be tested for 24 hours; After soaking, take out the sample to be tested and let it air dry naturally; Conduct UV test on the dried sample to be tested; After exposure to ultraviolet light, an accelerated aging test is performed, followed by a breaking force test and a resistance value test.

[0008] In one practicable manner, the process of conducting a UV test on a dry sample to be tested includes: Place the sample to be tested on a glass plate and illuminate it under a metal halide lamp with a power of 250±10W / m 2 In ultraviolet light environment, or choose a lamp power of 70-80W / m 2 Under ultraviolet light environment, the ultraviolet irradiation intensity is 2kWh / m 2 Ultraviolet test, in which the radiation intensity of the UVB band should account for 4-6%.

[0009] In one achievable method, an accelerated aging test is performed after exposure to ultraviolet light, and the process includes: After the UV exposure, an accelerated aging test was conducted at 120-150°C and 100% RH for 48 hours.

[0010] In one achievable manner, in step 4, the breaking force test process includes: During the test, the running speed of the tensile machine is 5-20mm / min, and the test area is extended 10cm at both ends with the overlap point of the sample to be tested as the center point.

[0011] In one achievable manner, in step 4, the resistance value testing process includes: The test area is formed by taking the overlap point of the sample to be tested as the center point and extending 10 cm to both ends.

[0012] In one achievable manner, in step 2, when the samples to be tested are initially tested, each sample to be tested is first visually inspected, and the results are recorded in sequence as YL1, YL2, ..., YLn; In step 3, when the samples to be tested are immersed in flux, half of the total number of samples to be tested are selected for flux immersion corrosion. Perform a visual inspection on each sample to be tested after immersion, and record the corrosion results in sequence as YYL1, YYL2, ... YYLn; By comparing the appearance of the sample before and after immersion, if corrosion is found after the test, it will be judged as unqualified.

[0013] In one achievable manner, during the sample preparation process in step 1, two welding strips are overlapped and welded, and the overlap size is 0.4-0.5 cm.

[0014] Compared with the prior art, the photovoltaic welding tape detection method provided by the present invention has the following beneficial effects: through a series of tests on photovoltaic welding tapes in a flux environment, the present invention can accurately verify the corrosion effect of flux on different welding tapes by replacing different welding tapes, and can also accurately verify the corrosion effect of different fluxes on photovoltaic welding tapes, thereby judging the influence of flux used in the production process of components on the reliability of photovoltaic welding tapes and photovoltaic components, which helps to standardize the safe and efficient use of flux, and has important guiding significance for the use of flux and welding tape in the production process of photovoltaic components. DETAILED DESCRIPTION

[0015] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] Flux is a chemical substance that is mainly used to assist welding. It can reduce welding temperature, promote welding flow, and reduce oxidation. However, flux is also corrosive and will have a certain impact on materials such as circuit boards and metals. In the production process of battery cells, welding processes are usually carried out, and flux is used to assist welding. If the flux remains on the surface or inside the battery cell, it may affect the performance of the battery cell.

[0017] The effects of flux corrosion on the cell mainly include the following aspects: ‌Reduced battery capacity‌: Flux residue may affect the chemical reaction inside the battery cell, resulting in reduced battery capacity‌.

[0018] ‌Accelerated self-discharge‌: The flux may produce certain chemical reactions, leading to accelerated self-discharge of the battery cell‌.

[0019] ‌Increase internal resistance‌: Flux residue may create additional resistance inside the battery cell, affecting the current output of the battery cell‌.

[0020] ‌ Impact on lifespan ‌: If there is too much flux residue or it is used improperly, it may have a certain impact on the lifespan of the battery cell.

[0021] The photovoltaic ribbon detection method provided by the present invention is used to detect the influence of flux on the performance of photovoltaic ribbon and photovoltaic module. The photovoltaic ribbon detection method includes sample preparation, initial test, flux immersion, environmental test, final test and performance evaluation.

[0022] Step 1: Sample preparation Cut 24 pieces of 20cm long welding ribbon or busbar; Two solder strips were randomly soldered with a 380-450℃ electric soldering iron to form 12 samples to be tested, with an overlap size of 0.4-0.5cm. After the two solder strips were overlapped, the test area was extended 10cm on both sides with the overlap point as the center point, and the rest was the clamping position of the fixture.

[0023] It is noted that 16 samples to be tested, or 24 samples to be tested, etc. may also be prepared. The number of samples to be tested for breaking force and the number of samples to be tested for resistance value measurement may be the same or different.

[0024] The samples to be tested are randomly numbered as L1, L2...L6, D1, D2...D6.

[0025] Extend 10 cm outward from the middle of the welding point and mark it with a marker for later testing.

[0026] Step 2: Initial testing Perform a visual inspection on the 12 samples to be tested and record them as YL1, YL2, ... YL12.

[0027] The breaking force test was carried out on L1, L2 and L3. During the test, the running speed of the tensile machine was 5-20mm / min, and the outer edge of the fixture was extended 10cm on both sides with the overlap point as the center point and flush with the mark to ensure that the length of the tested sample was 20cm. The results were recorded as LL1, LL2 and LL3.

[0028] Test the resistance values ​​of D1, D2 and D3. The outer edge of the electrode clamp of the digital micro-ohmmeter is flush with the mark. Ensure that the length of the sample to be tested is 20 cm. Record them as DZ1, DZ2 and DZ3.

[0029] Step 3: Flux Soaking Immerse L4, L5, L6, D4, D5, and D6 in flux, with 2-2.5 cm on both ends of the soldering ribbon exposed outside the flux to facilitate clamping with power clips and ensure conductivity. Apply a rated current of 12.5-13.5 for 24 hours.

[0030] The soldering strip is sprayed or coated with flux before soldering in order to improve the soldering effect. After soldering, the flux residue cannot be cleaned off, which will affect the performance and reliability of the product during long-term use.

[0031] The flux temperature should be maintained at 40-45°C, the general operating temperature of PV modules.

[0032] After the flux soaking is completed, take out the solder ribbon and let it dry naturally.

[0033] Step 4: Environmental testing Place the solder strip on the glass plate and place it under the power of the metal halide lamp at 250±10W / m 2 Under strong ultraviolet light, or the lamp power is 70-80W / m 2 In an environment with ultraviolet intensity, the ultraviolet light intensity is 2kWh / m 2 In the UV test, the proportion of UVB should meet 4-6%. This is to improve the test efficiency. The cumulative UV irradiance in the IEC61215-2:2021 standard is 15kWh / m 2 , UVB accounts for 3-10%.

[0034] After the UV exposure, an accelerated aging test was conducted at 121°C and 100% RH for 48 hours.

[0035] Step 5: Final test Carry out visual inspection on the 12 samples to be tested and record them as YYL1, YYL2, ..., YYLn.

[0036] The breaking force test was carried out on L4, L5 and L6. During the test, the running speed of the tensile machine was 5-20mm / min, and the outer edge of the fixture was extended 10cm on both sides with the overlap point as the center point and flush with the mark to ensure that the length of the tested sample was 20cm. The results were recorded as LL4, LL5 and LL6.

[0037] Test the resistance of D4, D5 and D6, taking the overlap point as the center point and extending 10 cm to both sides to ensure that the length of the sample is 20 cm. The outer edge of the electrode clamp of the digital micro-ohmmeter is flush with the mark and recorded as DZ4, DZ5 and DZ6.

[0038] Step 6: Performance evaluation: Initial Test Results Breaking force L = (LL1+LL2+LL3) / 3; Resistance value D initial = (DZ1 + DZ2 + DZ3) / 3; Final test results Breaking force Lfinal = (LL4+LL5+LL6) / 3; Resistance value Dfinal = (DZ4+DZ5+DZ6) / 3; Breaking force change rate Lchange = (Linitial - Lfinal) / Linitial; Resistance value change rate Dchange = (Dfinal-Dinitial) / Dinitial; If corrosion is found on the surface after the test, it will be judged as unqualified.

[0039] If the breaking force change rate L changes ≥ 5%, the soldering strip and flux are judged to be unsuitable.

[0040] If the resistance value change rate D is ≥5%, the soldering tape and flux are judged to be unsuitable.

[0041] Compared with the prior art, the photovoltaic welding tape detection method provided by the present invention has the following beneficial effects: through a series of tests on photovoltaic welding tapes in a flux environment, the present invention can accurately verify the corrosion effect of flux on different welding tapes by replacing different welding tapes, and can also accurately verify the corrosion effect of different fluxes on photovoltaic welding tapes, thereby judging the influence of flux used in the production process of components on the reliability of photovoltaic welding tapes and photovoltaic components, which helps to standardize the safe and efficient use of flux, and has important guiding significance for the use of flux and welding tape in the production process of photovoltaic components.

[0042] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A photovoltaic ribbon detection method, characterized in that: include: Step 1, sample preparation: Cut off several sections of welding strips of the same length, and randomly weld the welding strips together in pairs to form n samples to be tested, and randomly number them as L1, L2...L(n-1), Ln in sequence; n is a positive integer; Step 2: Initial test of the sample to be tested: Perform a breaking force test on n / 4 samples to be tested, and record the initial breaking force values ​​obtained in the test as LL1, LL2, ... LLx in sequence for breaking force test; x is a positive integer from 1 to n / 4; The resistance value of n / 4 samples to be tested is tested, and the initial resistance values ​​obtained by the test are recorded as DZ1, DZ2, ..., DZy in sequence; y is a positive integer from 1 to n / 4; Step 3: Test the sample after it is soaked in flux: The remaining samples to be tested are immersed in the flux and subjected to corrosion test; Step 4: simulate the actual application environment of the solder strip and conduct UV light and aging tests; Step 5: Test the results after corrosion: Perform a breaking force test on the remaining n / 4 samples to be tested, and record the final breaking force values ​​of the test as LL (x+1), LL (x+2) ... LL (x+x) in sequence; The remaining n / 4 samples to be tested are tested for resistance value, and the final resistance values ​​obtained from the test are recorded as DZ(y+1), DZ(y+2)...DZ(y+y) in sequence; Step 6: Based on the test results, evaluate the corrosion performance of the solder strip in the flux environment: Initial test results: Initial breaking force: Linitial = (LL1+LL2+…LLx) / x; Initial resistance value: D initial = (DZ1 + DZ2 + ... DZy) / y; Final test results: The breaking force of the welding strip after corrosion: Lfinal = (LL (x + 1), LL (x + 2) ... LL (x + x)) / x; Resistance value of the welding strip after corrosion: Dfinal = (DZ (y+1), DZ (y+2)…DZ (y+y)) / y; The change rate of the solder strip after being corroded by flux: The breaking force change rate of the welding strip after corrosion: Lchange = (Linitial - Lfinal) / Linitial; The resistance change rate after the welding strip is corroded is Dchange = (Dfinal-Dinitial) / Dinitial; If the breaking force change rate L changes ≥5%, the soldering strip and flux are judged to be unsuitable; If the resistance value change rate D is ≥5%, the soldering tape and flux are judged to be unsuitable.

2. The photovoltaic ribbon detection method according to claim 1, characterized in that: In step 3, the remaining samples to be tested are immersed in the flux, and the process of the corrosion test includes: Simulate the actual application environment of the solder strip, immerse the sample to be tested in the flux, and the flux temperature should be maintained at 40-45°C; and leave the clamping sections at both ends of the sample to be tested exposed outside the flux for easy detection and clamping; Clamp the clamping sections at both ends of the sample to be tested, and apply a rated current of 12.5-13.5I to the sample to be tested for 24 hours; After soaking, take out the sample to be tested and let it air dry naturally; Conduct UV test on the dried sample to be tested; After exposure to ultraviolet light, an accelerated aging test is performed, followed by a breaking force test and a resistance value test.

3. The photovoltaic ribbon detection method according to claim 2, characterized in that: In step 4, the process of conducting a UV test on the dried sample to be tested includes: Place the sample to be tested on a glass plate and illuminate it under a metal halide lamp with a power of 250±10W / m 2 In ultraviolet light environment, or choose a lamp power of 70-80W / m 2 Under ultraviolet light environment, the ultraviolet irradiation intensity is 2kWh / m 2 Ultraviolet test, in which the radiation intensity of the UVB band should account for 4-6%.

4. The photovoltaic ribbon detection method according to claim 2, characterized in that: In step 4, an accelerated aging test is performed after ultraviolet irradiation, and the process includes: After the UV exposure, an accelerated aging test was conducted at 120-150°C and 100% RH for 48 hours.

5. The photovoltaic ribbon detection method according to claim 1, characterized in that: In step 5, the breaking force test process includes: During the test, the running speed of the tensile machine is 5-20mm / min, and the test area is extended 10cm at both ends with the overlap point of the sample to be tested as the center point.

6. The photovoltaic ribbon detection method according to claim 1, characterized in that: In step 5, the resistance value test process includes: The test area is formed by taking the overlap point of the sample to be tested as the center point and extending 10 cm to both ends.

7. The photovoltaic ribbon detection method according to claim 1, characterized in that: Step 2: When the samples to be tested are initially tested, each sample to be tested is first visually inspected, and the results are recorded in sequence as YL1, YL2, ..., YLn; In step 3, when the samples to be tested are immersed in flux, half of the total number of samples to be tested are selected for flux immersion corrosion. In step 5, each sample to be tested is visually inspected after immersion, and the corrosion results are recorded as YYL1, YYL2, ..., YYLn in sequence; By comparing the appearance of the sample before and after immersion, if corrosion is found after the test, it will be judged as unqualified.

8. The photovoltaic ribbon detection method according to claim 1, characterized in that: Step 1: During sample preparation, two welding strips are overlapped and welded, with an overlap size of 0.4-0.5 cm.